Analisis Pengembangan Mata Pelajaran Muatan Lokal di Madrasah Ibtidaiyah Makrifatul Ilmi - Pitaloka , Lola; Wulandari, Yeni; pitaloka, lola (Limas PGMI, 2024)
This study aims to analyze the development of local content in Ma'arif school, with the formulation of the problem of analyzing the development of local content in Madrasah Ibtidaiyah Makrifatul Ilmi. The subject of the study was Madrasah Ibtidaiyah Makrifatul Ilmi Bengkulu Selatan, with the strengthening of local content of Muhadhoroh and Tahfizul Qur'an. Qualitative research methods by digging up information from curriculum representatives and teachers who are directly involved in Tahfizul Qur'an and Muhadhoroh activities. Furthermore, it was analyzed from interview and observation data in descriptive form. The results of the Tahfizul Qur'an Research with class provisions from Madrasah Ibtidaiyah Makrifatul Ilmi have a target to complete memorization, and are carried out routinely every Monday to Saturday. The method of developing local content is to straighten the intention, murotal every morning, get used to leading prayers, hifdzul jadid, takrir method, murojaah qorib method, muroja'ah ba'id method, Al-Qira'ah Al-Musta'mirah method, in the muhadoroh program which is held every Saturday at 09.00 am until finished. This Muhadroh event is carried out with various events presented by the students, starting from social drama that raises Islamic stories, poetry to pantun, regional dances, Islamic dances, sholawat or hadroh, tilawah, da'wah, music and singing, from the appearance of the students will be assessed directly by the ustadz and ustadzah as a form of evaluation and appreciation. This research provides insight into the development of local content at Madrasah Ibtidaiyah Makrifatul Ilmi South Bengkulu, especially in the Tahfizul Qur'an and Muhadhoroh programmes. Results show that these programmes not only focus on memorisation, but also develop students' speaking skills, creativity and spirituality. Suggested follow-ups include increased cooperation between teachers for more effective implementation strategies, training to optimise teaching methods, and parental and community involvement to strengthen religious culture and local wisdom.